2004
DOI: 10.1242/jeb.01259
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of twitch force by stretch in a nerve-skeletal muscle preparation of the frogRana porosa brevipodaand the effects of temperature on it

Abstract: SUMMARY We investigated the mechanism of the enhancement of twitch force by stretch and the effects of temperature on it in nerve-skeletal muscle preparations of whole iliofibularis muscles isolated from the frog Rana brevipoda. When a preparation was stimulated indirectly and stretched, the twitch force after the stretch was enhanced remarkably in comparison to that observed before a stretch at low temperature. The enhanced force obtained by a stretch of 20% resting muscle length (l0) at low te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, our observations are not novel. Ishii et al (2004) and Renaud and Stevens, (1981) also found essentially constant forces in frog skeletal muscles across a large range of temperatures. Frogs in these latter studies, like ours, were kept in a cold environment (about 5 1C) prior to testing, and it appears that frog muscles adapt to cold environments such that force can be kept constant over a large range of temperatures (Ishii et al, 2004).…”
Section: Temperature Effectsmentioning
confidence: 74%
“…However, our observations are not novel. Ishii et al (2004) and Renaud and Stevens, (1981) also found essentially constant forces in frog skeletal muscles across a large range of temperatures. Frogs in these latter studies, like ours, were kept in a cold environment (about 5 1C) prior to testing, and it appears that frog muscles adapt to cold environments such that force can be kept constant over a large range of temperatures (Ishii et al, 2004).…”
Section: Temperature Effectsmentioning
confidence: 74%
“…Although changes in muscle temperatures above 25°C significantly influence twitch force, they only have a small influence on tetanic force [27, 28]. To reduce the variability of collected force data, the temperature of the SM muscle was monitored regularly and maintained between 35-36°C.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature has been shown to affect many aspects of vertebrate function, including muscle contraction frequency, the maximum speed of locomotion, gas exchange and digestion rate (Huey and Bennett, 1987;Huey and Kingsolver, 1989;DeNardo et al, 2002;Ishii et al, 2004;Sollid et al, 2005). The effects of temperature on steady speed locomotion have been fairly well studied, particularly in ectotherms such as lizards and fish (Huey and Bennett, 1987;Garland, Jr and Losos, 1994).…”
Section: Introductionmentioning
confidence: 99%